Erratum: Hydraulic Characterization of a Pervious Concrete for Deep Draining Trenches (J. Mater. Civ. Eng DOI: 10.1061/(ASCE)MT.1943-5533.0002274) - Marzulli, Valentina; Cafaro, Francesco; Ziccarelli, Maurizio (Journal of Materials in Civil Engineering, 2022)
The following correction should be made to the original paper. The symbols in the legend of Fig. 9 are inverted. The empty circle should refer to the drying process. (Figure Presented). To preserve the published version of record, these details have been corrected only in this erratum.
CRIS-Team Scopus Importer:2024-12-16